Relative Contributions of Bed Load and Suspended Load to Sediment Transport Under Skewed‐Asymmetric Waves on a Sandbar Crest. Issue 2 (27th February 2019) - Mieras, Ryan S.; Puleo, Jack A.; Anderson, Dylan; Hsu, Tian‐Jian; Cox, Daniel T.; Calantoni, Joseph
Abstract: A large‐scale laboratory experiment was conducted to evaluate cross‐shore sediment transport and bed response on a sandbar under erosive and accretive field‐scale wave conditions (total of 11 cases). Unprecedented vertical resolution of sediment concentration was achieved through the use of conductivity concentration profilers alongside miniature fiber optic backscatter profilers. Observations were made of intrawave (phase‐averaged) and wave‐averaged cross‐shore sediment flux profiles and transport rates in the lower half of the water column on the crest of a sandbar. The net sediment transport rate was partitioned into suspended sediment (SS) and bed load (BL) components to quantify the relative contributions of SS and BL to the total sediment transport rate. Net SS transport rates were greater than net BL transport rates for the positive (wave crest) half‐cycle in 6 of 11 cases, compared to 100% (11 of 11) for the negative (wave trough) half‐cycle. Net (wave‐averaged) BL transport rates were greater, in magnitude, than net SS transport rates for 7 of the 11 cases. The dominant mode of transport was determined from the ratio of net BL to net SS transport rate magnitudes. The net transport rate was negative (offshore‐directed) when SS dominated and positive (onshore‐directed) when BL dominated. Net BL transport rate correlated well with third moments of free‐stream velocity ( r 2  = 0.72), suggesting that energetics‐type quasi‐steady formulae may be suitable for predicting BL transport under the range of test conditions. Plain Language Summary: Sandbars are nearshore features found at many beaches around the world, constantly changing shape and migrating seaward or landward with ever‐changing environmental conditions. A large‐scale experiment was carried out under controlled conditions to better understand the processes responsible for sandbar morphology. The amount of sand transported on a sandbar crest, per wave ( net ), was determined through detailed measurements of waves, water velocity, and the volume fraction of sand in the water at many elevations in the water column. Sand transport occurred in two distinct layers, one very near the sand bed (bed load) and the other spanning the majority of the water depth (suspended load). Whether sand was transported seaward or landward, per wave, was governed by whether more sand was transported in the suspended or bed load layer, respectively. Ultimately, this study will lead to improved predictive capability of morphologic evolution models in this highly dynamic, economically important region of the beach. Key Points: Bed load and suspended load transport rates were measured on a sandbar crest under field‐scale wave forcing Total net transport rate was offshore‐directed when suspended load dominated and onshore‐directed when bed load dominated Net bed load transport rates were well correlated with third moments of free‐stream velocity